De parientes, criados y gracias. Cultura del don y poder en el México colonial (siglos XVI-XVII) - Cañeque, Alejandro (Pontificia Universidad Católica del Perú. Fondo Editorial, 2005)
Through an analysis of concepts such as liberality, magnificence, distributivejustice, gratitude and “beneméritos de Indias,” this article aims to examine theideological foundations of the culture of favor and reward which permeated all levels of colonial society in the sixteenth and seventeenth centuries. At the same time, this culture of favor and reward formed the basis for the relationships of patronage established by the Crown to provide cohesion to the Spanish empire. The Crown attempted to reproduce in Mexico and Peru the patronage system through the figure of the viceroy. However, the viceroys enjoyed sufficient autonomy to allow them to utilize the system on their own behalf, something which would be the source of great troubles for the Crown.

A través de un análisis de conceptos como liberalidad, magnificencia, justicia distributiva, gratitud o beneméritos de Indias, este artículo examina los fundamentos ideológicos de la cultura del don que impregnaba todos los ámbitos de la sociedad colonial de los siglos XVI y XVII. Esta cultura del don, a su vez, formaba la base de las relaciones de patronazgo establecidas por la Corona española, las que daban cohesión al imperio hispano. La Corona intentó reproducir en México y en el Perú el sistema de patronazgo a través de la figura del virrey. Sin embargo, los virreyes disponían de la suficiente autonomía como para utilizar el sistema en su propio beneficio, lo cual produciría graves problemas a la Corona.
Keywords: Historia; https://purl.org/pe-repo/ocde/ford#6.01.01